Added pyridoxine for finishing-pig rations - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1976)
Pyridoxine added to finishing rations at two levels did not improve pig performance. Performance of pigs receiving a 20% crude protein broiler ration equalled, but was not better than, that of pigs receiving a standard 16% crude protein ration.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Pyridoxine; Finishing pigs; Crude protein ration